A balanced dual‐band bandpass filter with independently tunable differential‐mode frequencies. Issue 6 (30th March 2018) - Yang, Zhi‐Jie; Xiao, Guo‐Xian; Wei, Feng; Zhou, Bo; Li, Bin
Abstract: A balanced dual‐band bandpass filter (BPF) with independently tunable differential‐mode (DM) frequencies is proposed in this letter. The proposed BPF is composed of complementary split‐ring resonators (CSRRs) etched on the ground and varactors loaded on the resonators. A balanced stepped‐impedance microstrip‐slotline transition structure is introduced to transfer the DM signals successfully and block the common‐mode (CM) signals transmission. Good DM transmission and CM suppression can be achieved. Moreover, by changing the reverse bias voltages of the varactors loaded on coupling CSRRs, two DM resonant frequencies of the proposed balanced BPF can be tuned independently. To verify the feasibility of the design method, a balanced BPF with DM frequency ranging from 0.80 GHz to 1.12 GHz and 1.55 GHz to 2.05 GHz is fabricated and measured. Good agreement between the simulation and measurement results demonstrate the validity of the design.